Pembentukan Virtual Police dari Perspektif HAM di Indonesia - Rahardian Satya Mandala Putra; Felicia Tanalina Ylma; Azzahra Nabila Nurfirdaus (Jurnal Hukum Lex Generalis, 2021)
The Chief of Police of the Republic of Indonesia, through the Chief of Police Circular Letter/ 2/11/2021 concerning Ethical Cultural Awareness to Create a Clean, Healthy and Productive Indonesian Digital Space has placed an order for Virtual Police. The emergence of this unit caused a polemic on the responsibility of the state in guaranteeing the rights of the digital community. On the other hand, the Constitution of the Republic of Indonesia has the responsibility of the state in ensuring the protection, advancement, enforcement, and fulfillment of human rights. Moreover, Law Number 39 of 1999 concerning Human Rights also guarantees the state's recognition of human rights. This article aims to assess the suitability of the Virtual Police policy with the mandate of the Constitution and national and international laws on human rights.